Short and long-term phytoremediation capacity of aquatic plants in Cu-polluted environments. Issue 1 (January 2023) - Enochs, Brendan; Meindl, George; Shidemantle, Grascen; Wuerthner, Vanessa; Akerele, David; Bartholomew, Allison; Bulgrien, Benjamin; Davis, Abigail; Hoyt, Katelynn; Kung, Lena; Molina, Maria; Miller, Elias; et al.
Abstract: Freshwater ecosystems face numerous threats from human populations, including heavy metal contamination. Phytoremediation, the use of plants to remediate contaminated soils and sediments, is an effective and low-cost means of removing chemical contaminants, including heavy metals, from polluted environments. However, key questions remain unanswered in the application of this technology in aquatic environments, such as the long-term fate of pollutants following plant uptake. In this study, using two common wetland plant species (duckweed and tape grass), we first examined the capacity of plants to remove copper (Cu) from polluted water. Next, we evaluated the leaching potential of plant tissues following decomposition and how it is affected by a simulated freeze-thaw cycle. Using phytoremediated water and leachates from senesced plants we assessed phytoremediation success and Cu leaching potential by conducting standard toxicity assays using pond snails ( Physa acuta ), a species with known Cu sensitivity. We found that duckweed outperformed tape grass as a phytoremediator at low Cu concentrations. In addition, for plants grown in low concentrations of Cu, leaching from decaying plant material did not negatively impact snail survival, while at high concentrations of Cu, leaching did result in toxicity. Lastly, we found that a simulated freeze-thaw cycle increased the release of Cu from plant tissue in the presence of high Cu concentrations only, resulting in reduced snail survival. Our results indicate that in moderately Cu-polluted environments, some aquatic plants can remove contaminants without a long-term risk of leaching. In contrast, phytoremediation in highly polluted environments will likely require removal of plant tissue to prevent leaching of previously accumulated metals. Land managers must not only consider plant species and degree of contamination, but also geographic location, as freeze-thaw cycles may enhance plant decomposition and increase the likelihood of contaminant leaching following phytoremediation efforts in aquatic ecosystems.